A Prospective Study of Urinary Tract Infection in Children with Nephrotic Syndrome in a Tertiary Care Hospital - Dr.M.Bhuvaneswari; Dr.G.B.Meghana, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Introduction: Nephrotic Syndrome (NS) is among the most common chronic kidney diseases occurring in childhood. The incidence of idiopathic NS in Asian population is reported at 2-3 cases per 1,00,000 children. Defense mechanisms are impaired in patients with NS due to its consequences of tissue edema, urinary loss of immunoglobulin, complement and secondary effects to its treatment including steroids and other immunosuppressants. Immuno-compromised status of NS can result in increased susceptibility to various infections, which could be potentially serious and life-threatening without prompt diagnosis and treatment. Material and Methods: A prospective and descriptive study of all the patients with a diagnosis of nephrotic syndrome who attended to the Pediatric Outpatient Department (OPD) or were admitted at Department of Paediatrics, Surabhi Institute of Medical Sciences, Siddipeta, Telangana over a study period of one year from January 2024 to December 2024. 60 patients who have full filled the criteria of nephrotic syndrome (According to ISKDC) were included in the present study. The objective of the study were explained and written consent was obtained from the parents, prior to inclusion in the study. A detailed clinical examination was performed and findings were noted in the data sheet. Clean catch midstream urine samples were obtained from all the patients. Urine examination including routine analysis, microscopy, culture and sensitivity was done as per hospital standard policies. Results: The study was conducted over a period of 12 months and consisted of 60 children (40 males and 20 females). During this period, out of 60 children in the study nine had culture positive UTI (12 males and 6 females). The most common organism isolated from the urine culture was Escherichia coli followed by proteus, enterococcus, pseudomonas and Klebsiella, which was statistically significant (Binomial test p=0.043). Of the 18 cases who had culture positive UTI, 6 were newly diagnosed NS and 12 were relapse NS. There was no significant difference between the two groups with regard to sex and age distribution. Conclusion: We conclude that urinary tract infections are an important, but often under diagnosed infection in children with nephrotic syndrome. All children with nephrotic syndrome newly diagnosed or relapse should be screened for the presence of UTI.